Solarnomics : setting up and managing a profitable solar business - Wright, David, 1941- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Solar power has come of age. Not only has it become one of the key alternatives to fossil fuels, it can now be deployed in a way that makes a viable business with a financial profit. This book shows industry professionals and students how to do just that. Solarnomics describes the economics of building and operating a solar power plant today and provides a window into a future in which several technologies collaborate, and in which all participants in the electricity grid become smarter at scheduling both the supply and demand for electric power to give humanity a future that is sustainable, both environmentally and economically. The book shows how to estimate costs and revenues, how to tweak the design of a project to improve profitability, how to calculate return on investment, how to assess and deal with risk, how to raise capital, how to combine solar with batteries to make a hybrid microgrid, and how to be prepared for future developments in the evolving smart electricity grid. Solarnomics will enable professionals in the solar industry to assess the potential profitability of a proposed solar project, and it will enable students to add an extra dimension to their understanding of sustainability"--
Utility-scale : large solar -- Behind-the-meter : commercial and industrial, medium sized solar -- Behind-the-meter : small business and residential, small solar -- Off-grid : small to large solar -- Net present value, NPV and internal rate of return, IRR -- Levelized cost of electricity, LCOE -- Solar finance -- Managing risk -- Storage : improving solar profitability -- Profitability of solar microgrids and hybrids -- Extra revenue from grid balancing services -- Participative/transactive electricity markets -- Emerging solar technologies -- Emerging solar applications -- Profitability analysis for emerging solar technologies.
Keywords: Solar energy industries -- Finance; Solar power plants -- Management; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Industries / Energy Industries; BUSINESS & ECONOMICS / Green Business